Yayasan UMP distributes Back To School contributions by appointment - Nor Salwana, Mohammad Idris (2021)
KUANTAN, 14 January 2021 – A total of 104 children of Universiti Malaysia Pahang (UMP) staff received a contribution of school necessities from Yayasan UMP upon the university concern in alleviating the school expenses of children of underprivileged staff.